2020
DOI: 10.1186/s12891-020-3082-2
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel surgery: predictors of clinical outcomes and patients’ satisfaction

Abstract: Background: Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy. Moreover, carpal tunnel release (CTR) surgery generally has excellent results. The present study aimed to investigate the predictors of clinical outcomes and satisfaction in patients with CTR. Methods: In this observational prospective cohort study, 152 patients with open carpal tunnel release surgery were investigated. Complete clinical examinations were performed and recorded before the surgery, two weeks after the surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
(33 reference statements)
1
25
0
2
Order By: Relevance
“…The probability of no improvement or deterioration after surgery was 0.1 for the age of 30, while this reached 0.9 for the age of 80 in our study. Similarly, poorer surgical results in older patients have been shown in many studies ( 36 , 39 , 41 , 42 ). Others have not found any relationship between postoperative results and older age ( 22 , 37 , 43 ).…”
Section: Discussionmentioning
confidence: 62%
“…The probability of no improvement or deterioration after surgery was 0.1 for the age of 30, while this reached 0.9 for the age of 80 in our study. Similarly, poorer surgical results in older patients have been shown in many studies ( 36 , 39 , 41 , 42 ). Others have not found any relationship between postoperative results and older age ( 22 , 37 , 43 ).…”
Section: Discussionmentioning
confidence: 62%
“…[ 18 ] reported cases of ADEM following COVID-19 while Abdi et al . [ 19 ] reported the ADEM case without prominent clinical pulmonary symptoms. The case reported by Utukuri et al .…”
Section: Resultsmentioning
confidence: 99%
“…Novi et al, [14] Parsons et al, [15] Zoghi et al, [16] Zanin et al, [17] and Zhang et al [18] reported cases of ADEM following COVID-19 while Abdi et al [19] reported the ADEM case without prominent clinical pulmonary symptoms. The case reported by Utukuri et al [20] had no respiratory symptoms of COVID-19 while Reichard et al [21] described the case where ADEM was confirmed by autopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Symptom severity and longer symptom duration were reported as predictors of poor outcomes after conservative management 44 or surgery. 49 In contrast, Meys et al 29 found that symptom duration was not associated with outcome after steroid injection. Although younger age was shown to be an independent predictor of higher postoperative satisfaction, 49,50 one study revealed that old age was a good outcome predictor after conservative treatment.…”
Section: Although Other Characteristics Have Been Reported As Predictorsmentioning
confidence: 97%
“…49 In contrast, Meys et al 29 found that symptom duration was not associated with outcome after steroid injection. Although younger age was shown to be an independent predictor of higher postoperative satisfaction, 49,50 one study revealed that old age was a good outcome predictor after conservative treatment. 27 Bowman et al 51 reported that sex and the dominant hand were outcome predictors when treating CTS, in which males and the dominant hand had poor outcomes.…”
Section: Although Other Characteristics Have Been Reported As Predictorsmentioning
confidence: 97%